PENGARUH RESPONS KRISIS MECIMAPRO PADA KONSER DAY6 FOREVER YOUNG IN JAKARTA DAN BRAND ATTITUDE TERHADAP CUSTOMER PURCHASE INTENTION - Nur Fitriana Ananda; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This study was motivated by the massive number of consumer complaints on social media andnegative press coverage regarding Mecimapro’s crisis response during the DAY6 “ForeverYoung” concert in Jakarta. These circumstances led various consumer evaluations ofMecimapro as a concert promoter. The purpose of this study is to analyze the influence of crisisresponse and brand attitude on customer purchase intention. This study is grounded inSituational Crisis Communication Theory and the Theory of Reasoned Action, employing aquantitative approach and involving 106 respondents who had attended an event organized byMecimapro. Data analysis utilized multiple linear regression through SPSS. The resultsindicate that Mecimapro’s crisis response during the DAY6 “Forever Young” concert in Jakartaand brand attitude have a positive and significant influence on customer purchase intention,with significance levels of 0.000 and 0.001, respectively. This means that the better a brand’scrisis response and the more positive the consumers’ brand attitude, the higher the consumers’purchase intention toward that brand. Conversely, a decline in either of these variables tends tobe followed by a decrease in customer purchase intention. Therefore, Mecimapro needs todevelop a well-planned crisis communication management SOP and consistently build brandattitude through improvements in facility and service quality.